DRAMATURGI PENYANDANG OLIGODAKTILI - Sulaeman Sulaeman (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The purpose of this research it is analyzing the management of the impression in the stage before it or the stage back displayed in the process of communication at the daily life of social interaction with the surrounding environment for people with oligodactyly in Kampung Ulutaue. This research uses the method interpretative subjective with the approach dramaturgy, involving fifteen informants with ten men and five women were chosen purposively.Researchers are digging experience social interaction informants was conducted using data collected through in-depth interviews and observation participatory with the data supporting based on perspective the act of social and dramaturgy. The results of the study explain people oligodactyly manage the impression upon a stage before or the stage behind with verbal communication and nonverbal displayed social interaction in the process of communication with fellow people oligodactyly, family, the community government agencies, and television treating them by creating inconveniences in exertion to survive, weaken psychology self, marginalisation, traumatic, and self-denial its environment from suffering experienced. The contribution of the study is giving insight about impression management on people with oligodactyly by using dramaturgy perspective.